2023
DOI: 10.5851/kosfa.2022.e71
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrite and Phosphate Replacements for Clean-Label Ground Pork Products

Abstract: Ethics approval (IRB/IACUC) (This field may be published.)This manuscript does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Similarly, Jeong et al (2020b) showed that the CIE b* values of pork products cured with 0.35% ground Chinese cabbage powder increased. However, the CIE b* values of the FRJP and CRP treatments did not differ (p > 0.05) from those of the control, which aligns with the previous findings by Yoon et al (2023) for pork sausages cured with ground radish powder. Sebranek and Bacus (2007) suggested that plant powders with less distinctive pigments would more effectively facilitate the supply of natural sources of nitrate.…”
Section: Quality Characteristics Of Pork Sausages Cured With Differen...supporting
confidence: 89%
“…Similarly, Jeong et al (2020b) showed that the CIE b* values of pork products cured with 0.35% ground Chinese cabbage powder increased. However, the CIE b* values of the FRJP and CRP treatments did not differ (p > 0.05) from those of the control, which aligns with the previous findings by Yoon et al (2023) for pork sausages cured with ground radish powder. Sebranek and Bacus (2007) suggested that plant powders with less distinctive pigments would more effectively facilitate the supply of natural sources of nitrate.…”
Section: Quality Characteristics Of Pork Sausages Cured With Differen...supporting
confidence: 89%
“…In contrast, treatments 1-4, which used natural additives, demonstrated higher (p<0.05) cooking loss than the control (+) (Table 2). Previous research conducted by Choi et al (2014) and Yoon et al (2023) indicated that replacing phosphate with oyster shell powder in pork ham or sausages did not result in a significant difference in cooking loss compared with conventional meat products. However, the findings from this study on pork patties differ from these previous results, suggesting that the replacement of phosphate with OP may have a different effect on cooking loss for this particular type of product.…”
Section: Results and Discussion Ph And Cooking Lossmentioning
confidence: 87%
“…Also, the substitution of nitrite with alternative natural ingredients in meat products has gained considerable interest in recent years, regarding the potential health risks associated with nitrite consumption while still ensuring the safety and quality of the final products. Various natural ingredients have been explored as potential replacements for nitrite, such as celery powder, beetroot powder, and sea salt, among others [31,101,[116][117][118][119][120]. These ingredients contain naturally occurring nitrates, which can be converted into nitrites during the curing process.…”
Section: Nitrites/nitrates On Healthier Meat Productsmentioning
confidence: 99%
“…As the demand for healthier and more natural food options continues to rise, it is essential to keep consumers informed about the use of nitrate and nitrite substitutes in meat products; providing transparent labeling and accurate information empowers consumers to make informed choices and encourages the industry to prioritize their health. The availability of a growing number of "clean" label ingredients provides a new suite of approaches that are available for application by meat processors to help overcome some of the negative connotations associated with processed meat products [120,126,127].…”
Section: Nitrites/nitrates On Healthier Meat Productsmentioning
confidence: 99%